Modeling heterogeneous behaviors with different strategies in a terrorist attack - Le Bi; Tingting Liu; Zhen Liu; Jason Teo; Yumeng Zhao; Yanjie Chai (Elsevier B.V., 2022)
Existing simulations of terrorist attacks do not consider individual variations. To overcome this limitation, we propose a framework to model heterogeneous behavior of individuals during terrorist attacks. We constructed an emotional model that integrated personality and visual perception for pedestrians. The emotional model was then integrated with pedestrian relationship networks to establish a decision-making model that supported pedestrians’ altruistic behaviors. A mapping model has been developed to correlate antisocial personality traits with attack strategies employed by terrorists. Experiments demonstrate that the proposed algorithm can generate practical heterogeneous behaviors that align with existing psychological research findings.